Clinical Utility of Multi‐Energy Spectral Photon‐Counting Computed Tomography in Crystal Arthritis. Issue 7 (28th May 2019) - Stamp, Lisa K.; Anderson, Nigel G.; Becce, Fabio; Rajeswari, Maya; Polson, Matthew; Guyen, Olivier; Viry, Anais; Choi, Chloe; Kirkbride, Tracy E.; Raja, Aamir Y.
Abstract : Objective: To determine whether novel multi‐energy spectral photon‐counting computed tomography (SPCCT) imaging can detect and differentiate between monosodium urate (MSU), calcium pyrophosphate (CPP), and hydroxyapatite (HA) crystal deposits ex vivo. Methods: A finger with a subcutaneous gouty tophus and a calcified knee meniscus excised at the time of surgery were obtained. The finger was imaged using plain x‐ray, dual‐energy CT (DECT), and multi‐energy SPCCT. Plain x‐ray and multi‐energy SPCCT images of the meniscus were acquired. For validation purposes, samples of the crystals were obtained from the tophus and meniscus, and examined by polarized light microscopy and/or x‐ray diffraction. As further validation, synthetic crystal suspensions of MSU, CPP, and HA were scanned using multi‐energy SPCCT. Results: Plain x‐ray of the gouty finger revealed bone erosions with overhanging edges. DECT and multi‐energy SPCCT both showed MSU crystal deposits; SPCCT was able to show finer detail. Plain x‐ray of the calcified meniscus showed chondrocalcinosis consistent with CPP, while SPCCT showed and differentiated CPP and HA. Conclusion: Multi‐energy SPCCT can not only detect, differentiate, and quantify MSU crystal deposits in a gouty finger ex vivo, but also specifically detect, identify, and quantify CPP within an osteoarthritic meniscus, and distinguish them from HA crystal deposits. There is potential for multi‐energy SPCCT to become useful in the diagnosis of crystal arthropathies.